Meningkatkan Dimensi Bergotong Royong dalam Belajar PAK-BP dengan Model PBL Materi Pribadi Yang Tumbuh dan Berkembang Fase B Kelas IV SDN 16 Panoalatn - M. Indah Puspitarini; Fr. Wuriningsih; Budi Hartana (Sekolah Tinggi Pastoral Kateketik (STPKat) Santo Fransiskus Assisi Semarang, 2024)
The changes of the times may result in a shift in the values of life for individuals or even groups of people. However, most members of society who are not significantly affected by these changes continue to use